Tert-Butyl(3-cyano-4, 6-dimethylpyridin-2-yl)carbonate as a green and chemoselective N-tert-butoxycarbonylation reagent. (8th April 2019) - Du, Fangyu; Zhou, Qifan; Fu, Yang; Zhao, Hanqi; Chen, Yuanguang; Chen, Guoliang
Abstract : The use of tert -butyl(3-cyano-4, 6-dimethylpyridin-2yl) carbonate as a chemoselective tert -butoxycarbonylation reagent for aromatic and aliphatic amines has been demonstrated (30 examples). Abstract : The use of tert -butyl(3-cyano-4, 6-dimethylpyridin-2-yl)carbonate as a chemoselective tert -butoxycarbonylation reagent for aromatic and aliphatic amines has been demonstrated. To gain insight into this reaction, in situ React IR technology was used to confirm the effectivity and chemoselectivity of this novel Boc reagent. The reaction was carried out chemoselectively in high yield under mild, environment-friendly conditions and was completed quickly within 1 hour. Simultaneously, the Boc carrier was easily recyclable, and has great application prospects for industrial production.